Successful process improvement projects are no accidents. Issue 11 (1st October 2015) - Calderon, Natalja Nikitina; Kajko‐Mattsson, Mira; Nolan, Andrew James
Abstract: Despite substantial amount of research in software process improvement (SPI) and a wide variety of SPI approaches and software process maturity models, many of the SPI initiatives still fail. This is mainly because the improvement projects are found to be far more complex than expected from the beginning. They embrace a myriad of various organizational, managerial, process, and social properties that need to be considered, such as clear directions, full commitment, continuous sponsorship, and dedicated resources. Some of those properties have been already widely known within SPI arena while others have not yet been recognized. This paper identifies the properties that need to be fulfilled for making SPI projects successful and puts them into an SPI Checklist to be used in the assessment of SPI projects. It then reports on its pilot evaluation within 10 SPI projects at Rolls Royce . The evaluation results show a strong relationship between the fulfillment of the checklist items by the projects studied and the success rates of those projects. Thereby, the results provide a strong proof of concept demonstrating that the success of SPI projects is no accident but a foreseeable outcome of clearly identified and assessable characteristics. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The paper identifies the properties of successful software process improvement (SPI) projects and puts them into a checklist. It reports on the pilot evaluation of the checklist within 10 SPI projects at Rolls Royce. The evaluation results show a strong relationship between the fulfillment of the checklist items by the projects studied and the success rates of those projects. Thereby, the results demonstrate that the success of SPI projects is no accident but a foreseeable outcome of clearly identified and assessable characteristics.